Preparation and characterization of copper nanoparticles surface‐capped by alkanethiols. (18th October 2013) - Yang, Guangbin; Zhang, Zhanming; Zhang, Shengmao; Yu, Laigui; Zhang, Pingyu; Hou, Yanchao
Abstract : Cu nanoparticles surface‐capped by alkanethiols were synthesized using ligand exchange method in a two‐phase system. The effects of synthetic conditions, including the pH value of CuSO4 solution, the ratio of cetyltrimethyl ammonium bromide to CuSO4, and reaction temperature, on the size and shape of as‐synthesized Cu nanoparticles were investigated. As‐synthesized Cu nanoparticles surface‐capped by alkanethiols with different chain lengths (C x S‐Cu) were characterized by means of X‐ray diffraction, transmission electron microscopy, Fourier transform infrared spectrometry, and ultraviolet–visible light spectrometry. The tribological behavior of C x S‐Cu as an additive in liquid paraffin was evaluated with a four‐ball machine. Results indicate that cetyltrimethyl ammonium bromide plays an important role in controlling the dispersion of Cu nanoparticles before adding modifier octanethiol into the reaction solution. C x S‐Cu nanoparticles as additive in liquid paraffin possess excellent antiwear and friction‐reduction performance because of the deposition of nano‐Cu with low melting point on worn steel surface leading to the formation of a self‐repairing protective layer thereon. Copyright © 2013 John Wiley & Sons, Ltd.